Review article: Constraints on policy transfer - David Benson (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
Policy transfer and its analogous term lesson drawing have received widespread and continuing attention in the public policy literature. To date, most theoretical and analytical approaches have centred on exploring the characteristics or mechanics of policy transfer, or promoting this concept as a normative project for improving policy-making. Surprisingly less attention has been given to systematically theorising the actual constraints on this process despite inherent and widely recorded difficulties with undertaking policy transfer in practice. This paper therefore reviews the policy transfer literature to draw out critical constraints, classifying them according to their position in the transfer process: demand-side constraints; programmatic constraints; contextual constraints; and, application constraints. One feature of the literature to date is how these constraints have primarily been related to 'hard' policy transfer, peer-to-peer between national governments. This paper therefore begins to examine how constraints for 'soft' policy transfer manifest themselves across the increasingly multi-levelled, collaborative and networked political landscape of contemporary governance; under the wire of national government control. Further development of this theoretical framework could aid the assessment of policies/lessons for potential transfer.
Keywords: 330; lesson drawing; policy transfer; constraints; hard policy; soft policy; peer-to-peer transfer; Politische Entscheidung; Wissenstransfer; Internationale Zusammenarbeit; Theorie